Asylum and Irregular Maritime Migration in The Canary Islands - Mesa-Pérez, Carmelo Ulises; Poy, Arnau (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
This article explores the relationship between irregular maritime arrivals and asylum applications in the Canary Islands during the period from 2018 to 2023. It investigates whether the increase in maritime arrivals has led to a rise in the number of asylum applications. To this end, a descriptive analysis of statistical data from various sources has been conducted. This analysis has been complemented with qualitative empirical material collected from two fieldworks. The article engages with current academic debates surrounding the West African Route, access to asylum in Spain, and the theoretical perspective of the “deterrence paradigm.” The empirical results reveal a gap between the number of irregular arrivals and the number of asylum applications in the Canary Islands, as well as some circumstances that have restricted access to asylum. Furthermore, it identifies certain theoretical limitations of the deterrence paradigm in analysing the Canary case and proposes potential future lines of research.